Analisis Penggunaan Kata Makian Panggilan Seseorang dalam Bahasa Serawai Desa Tebat Gunung Kecamatan Semidang Alas Kabupaten Seluma - Sukaisi, Selti; Kasmantoni, Kasmantoni; Friantary, Heny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This study aims to examine the use of curse words in the Serawai language in Tebat Gunung Village, Semidang Alas District, Seluma Regency. The study focuses on the forms and meanings of curse terms used by the local community, thereby contributing to a broader understanding of language as a medium for expressing ideas and thoughts in accordance with linguistic norms. The method employed is qualitative research with a descriptive approach, aiming to deeply and comprehensively understand the studied phenomenon. The results show that curse words remain a significant part of daily communication among the Serawai community. These words are used in emotional contexts, such as insults or mockery, as well as in joking contexts. A total of 60 curse words were identified during the study in Tebat Gunung Village. In conclusion, curse words in the Serawai language reflect the unique cultural habits of the local community, which should be viewed in their social and cultural context. Keywords: Serawai Language, Tebat Gunung Village, Curse Words